PERILAKU MEROKOK PADA ANAK USIA SEKOLAH (Studi Kasus Pada Remaja SMK Daerah Situbondo Kecamatan Panji Kabupaten Situbondo) - Utami, Novitasari Dwi; Suhartini, Elly (Jurnal ENTITAS SOSIOLOGI, 2018)
Smoking behavior in school-aged children is the result of interaction with their environment, even with people who have consumed cigarettes. The main reason for teen smoking is the emergence of curiosity in cigarettes and the expression of male identity through cigarettes. Families, peer groups and schools are supporting contexts for teenagers to smoke. The purpose of this study was to determine, analyze and describe smoking behavior in school-aged children. The research method used descriptive, a qualitative method with a purposive sampling technique. From this study, it was found that families gave permission to teenagers to smoke in order to make it easier in controlling children and that schools provided an opportunity for them to smoke. Keywords: Smoking Behavior, Smoking Process, Supporting Context of Teen Smoking